Assessment of the application for renewal of authorisation of Bactocell® (Pediococcus acidilactici CNCM I‐4622) as a feed additive for all fish and shrimps and its extension of use for all crustaceans. (26th April 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Bactocell ® is the trade name for a feed additive based on viable cells of a strain of Pediococcus acidilactici . Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on Bactocell ® in the context of the renewal of the authorisation for shrimps, salmonids and fish other than salmonids. In addition, the applicant requested the extension of use for all crustaceans. The applicant has provided evidence that the additive currently in the market complies with the existing conditions of authorisation. The FEEDAP Panel concludes that Bactocell ® Aqua 10 Md/100 Md is safe under the current conditions of authorisation for the target species (all fish, shrimps and all crustaceans), consumers of products from animals fed the additive and the environment. Bactocell ® Aqua 10 Md/100 Md is non‐irritant to skin and eyes and is not a dermal sensitiser, but should be considered a potential respiratory sensitiser. Exposure of users by inhalation is very likely. There is no need for assessing the efficacy of Bactocell ® in the context of the renewal of the authorisation. The Panel concludes that the additive at the minimum inclusion level of 1 × 10 9 CFU/kg feed has the potential to be efficacious in salmonids and in the new species proposed, i.e. all crustaceans.